Endovascular Treatment of Intracranial Arteriovenous Malformations with Onyx: Technical Aspects - Weber, W.; Kis, B.; Siekmann, R.; Kuehne, D. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We report our experiences in the treatment of intracranial arteriovenous malformations (AVMs) with Onyx embolization before neuro- or radiosurgery, focusing on the embolization technique with Onyx.METHODS: Ninety-three patients (40 women and 53 men, mean age 38 years) with 94 intracranial AVMs with a mean volume of 9.2 mL were embolized with Onyx. The following features of all AVMs were evaluated before the treatment: type of nidus and shunt, draining veins, and feeding arteries.RESULTS: Complete obliteration rates were 20% at the end of all embolization steps and 53% after embolization and surgery. In 21% of patients the final control angiography is not yet available (after surgery 9%, after radiosurgery 12%). In 4% of patients, radiosurgery was planned due to a persistent arteriovenous shunt. The injection of Onyx resulted in high occlusion rates (volume reduction >90%) when the AVM was in a supratentorial and cortical location, the nidus was compact and plexiform, and when there was a small number of supplying (direct) feeders and one superficial draining vein. Access device–related complications (stuck catheter, vessel perforation) occurred during the embolization of 220 feeding arteries in 6% of patients, with all such instances having had no clinical consequences.CONCLUSION: With knowledge of the morphologic characteristics of AVMs that are suitable for a treatment with Onyx, high occlusion rates and low complication rates in treating a small number of feeders are feasible. Superselective intranidal or perinidal catheter positions and slow, controlled injections that protect the draining veins make the therapy safe even in complex AVMs and critical locations.